Finned Surfaces: Convection: Heat Transfer Between A Solid Surface and A Moving Fluid Is Governed by The
Finned Surfaces: Convection: Heat Transfer Between A Solid Surface and A Moving Fluid Is Governed by The
Finned Surfaces: Convection: Heat Transfer Between A Solid Surface and A Moving Fluid Is Governed by The
FINNED SURFACES
Introduction:
Convection: Heat transfer between a solid surface and a moving fluid is governed by the
Newton’s cooling law: Q = hA(T − T ) where Ts is the surface temperature and T is the
s ∞
fluid temperature. Therefore, to increase the convective heat transfer, one can
• Increase the temperature difference (T − T ) between the surface and the fluid.
s ∞
• Increase the convection coefficient h. This can be accomplished by increasing the fluid
flow over the surface since h is a function of the flow velocity and the higher the velocity,
the higher the h. Example: a cooling fan.
• Increase the contact surface area A. Example: a heat sink with fins.
Many times, when the first option is not in our control and the second option (i.e. increasing h) is
already stretched to its limit, we are left with the only alternative of increasing the effective
surface area by using fins or extended surfaces. Fins are protrusions from the base surface into
the cooling fluid, so that the extra surface of the protrusions is also in contact with the fluid.
Most of you have encountered cooling fins on air-cooled engines (motorcycles, portable
generators, etc.), electronic equipment (CPUs), automobile radiators, air conditioning equipment
(condensers) and elsewhere.
Let us take small element dx on a rectangular fin with uniform cross sectional area A
Q =Q +Q
x x + dx conv
dT dT d dT dT d 2T
Q = −k A Q = −k A + − k A dx = − k A − k A 2 dx
x dx x + dx dx dx dx dx dx
Q
conv
= h A T −T
s ∞
( ) Q
conv
(
= h ( P dx) T − T
∞
) As = ( permeter ) dx
Q =Q +Q
x x + dx conv
−k A
dT
dx
= −k A
dT
dx
d 2T
− k A 2 dx + h ( P dx) T − T
dx ∞
( )
kA
d 2T
dx 2
(
dx = h ( P dx) T − T
∞
)
d 2T h P
dx 2
=
KA
T −T
∞
( )
d 2T
dx 2
= m2 T − T(
∞
) m=
hP
KA
m2 =
hP
KA
d 2θ ( x) let θ ( x) = T − T∞
− m 2 θ ( x) = 0
dx 2 dθ ( x) dT
=
dx dx
This equation is called, one dimensional fin equation for fins of uniform cross section(second
order, linear, ordinary equation)
θ ( x) = C1 cosh mx + C 2 sinh mx
C1 and C2 are constant are determined by the application of the two boundary condition, one
specified for the fin tip.
x= 0 at T=Tb and the other boundary condition there are several possibities
d 2θ (t )
2
− m 2 θ (t ) = 0
dx
θ (t ) = C1e − mx + C 2 e mx
Boundary conditions, x = 0 at T = T θ = Tb − T∞
b b
x = ∞ at T = T = T θ =0
L ∞ L
x = 0 at T = T θ = Tb − T∞
b b
θ = C1
b
x = ∞ at T = T = T θ = 0
L ∞ L
0 = C2∞ C2 = 0
θ ( x) = θ e − mx
b
θ ( x) −mx
=e
θ
b
T −T
∞ = e − mx
T −T
b ∞
Heat transfer rate
dT dθ ( x ) θ ( x) −mx
Q =−k A =−k A =e
dx x = 0 dx x = 0 θ
b
Q = − k A(− mθ b ) θ ( x) = θ b e − mx
Q = k A mθ b dθ ( x )
= − mθ b e − mx
hP dx
Q=kA (Tb − T∞ )
KA
Fin of finite length with insulated tip (short fin with end insulated)
d 2T
dx 2
(
= m2 T − T
∞
) m=
hP
KA
m2 =
hP
KA
let θ ( x) = T − T∞
d 2θ ( x)
− m 2 θ ( x) = 0
dx 2 dθ ( x) dT
=
dx dx
Boundary conditions, x = 0 at T = T θ b = Tb − T∞
b
dθ
x = L at =0
dx
x = 0 at T = T θ = Tb − T∞
b b
θ ( x) = C1 cosh mx + C 2 sinh mx
θ = C1
b
dθ (t )
= θ m sinh (mx ) + C 2 m cosh (mx )
dx b
− θ b sinh (mL )
θ (t ) = θ cosh mx + sinh mx
b cosh (mL )
θ (t ) sinh (mL )
= cosh mx − sinh mx
θ
b cosh (mL )
T −T
∞ = cosh m(L − x )
T −T cosh (mL ) (Refer HMTDB Page No 50)
b ∞
dT dθ ( x ) θ ( x) cosh m(L − x )
Q =−k A =−k A =
dx x = 0 dx x = 0 θ cosh (mL )
b
cosh m(L − x )
θ θ ( x) = θ b
Q = − k A − b m [sinh m(L − x )] cosh (mL )
cosh (mL )
x =0 dθ ( x ) θ
= b m [sinh m(L − x )](0 − 1)
θ dx cosh (mL )
Q = k Am b sinh mL
cosh (mL ) θ
dθ ( x )
=− b m [sinh m(L − x )]
cosh (mL )
( )
Q = k Am T − T tanh mL
b ∞
dx
b ∞
(
Q = hPKA T − T tanh mL ) (Refer HMTDB Page No 50)
L
Q = ∫ h ( P dx) (T ( x) − T ) (Refer the method of last derivation)
∞
o
d 2θ ( x)
− m 2θ ( x) = 0
dx 2
Boundary conditions
θ ( x) = T − T =θ at x=0
b ∞ 0
dθ ( x )
k + h θ ( x) = 0 at x=L
dx L
Solution for the second order differential equation
θ ( x) = C cos h (m x) + C sin h (m x)
1 2
θ ( x) = T − T =θ at x = 0
b ∞ 0
θ ( x) = C cos h (m x) + C sin h (m x)
1 2
θ =C + 0 θ =C
0 1 0 1
dθ ( x )
dθ ( x ) at x=L − kA = h Aθ ( x )
k + h θ ( x) = 0 dx x = L L x=L
dx L
θ ( x) = θ cos h (m x) + C sin h (m x)
0 2
dθ ( x )
= θ m sin h (m x) + C m cos h (m x)
dx 0 2
dθ ( x )
k + h θ ( x) = 0 at x=L
dx L
h
θ sin h (m L) + L cos h (m L)
0 mk
C2 = −
h
cos h (m L) + L sin h (m L)
mk
h
sin h (m L) + L cos h (m L)
mk
θ ( x) = θ cosh (m x) − θ 0 sin h (m x)
0 h
cos h (m L) + L sin h (m L)
mk
h
sin h (m L) + L cos h (m L)
θ ( x) mk
= cos h (m x) − sin h (m x)
θ h
0 cos h (m L) + L sin h (m L)
mk
h h
cos h (m x) cos h (m L) + L sin h (m L) − sin h (m L) + L cos h (m L) sin h (m x)
θ ( x)
= mk mk
θ h
0 cos h (m L) + L sin h (m L)
mk
h h
cos h (m x) cos h (m L)+ L sin h (m L) cos h (m x) − sin h (m L) sin h (m x) + L cos h (m L) sin h (m x)
θ ( x) mk mk
=
θ h
0 cos h (m L) + L sin h (m L)
mk
h h
[cos h (m L) cosh (m x) − sin h (m L) sin h (m x)] + L sin h (m L) cos h (m x) − L cos h (m L) sin h (m x)
θ ( x)
= mk mk
θ h
0 cos h (mL) + L sin h (m L)
mk
h
[cosh m( L − x) ] + L [sin h m( L − x)]
θ ( x) T ( x) − T∞ mk
= =
θ T −T h
0 b ∞ cos h (mL) + L sin h (m L)
mk
dT dθ ( x )
Q =−k A =−k A
dx x = 0 dx x = 0
h
[cos h m( L − x) ] + L [sin h m( L − x)]
mk
θ ( x) = θ 0
h
cos h (m L) + L sin h (mL)
m k
hL
[m sin h m( L − x)(−1) ] + [m cosh m( L − x)(−1)]
dθ ( x ) mk
= θ0
dx h
cos h (m L) + L sin h (m L)
mk
h
[m sin h m( L − x)(−1) ] + L [m cosh m( L − x)(−1)]
mk
Q = − k Aθ
0 h
cos h (m L) + L sin h (m L)
mk x=0
hL
[− m sin h (mL) ] − [m cosh (mL)]
mk
Q = − k Aθ 0
h
cos h (m L) + L sin h (m L)
mk
hL
sin h (mL) + cosh (m L)
mk
Q = k Amθ 0
hL
cos h (m L) + sin h (m L)
mk
hL
sin h (mL) + cosh (m L)
Q = Ph k A T − T
L b
(∞
) mk
hL
cos h (m L) + sin h (m L)
mk
Temperature distribution
d 2θ ( x)
− m 2θ ( x) = 0
dx 2
Boundary conditions
T =T at x = 0 θ = T −T
b b b ∞
T =T at x = L θ = T −T
L L L ∞
θ ( x) = C cos h (m x) + C sin h (m x)
1 2
T =T at x = 0 θ = T −T
b b b ∞
θ ( x) = C cos h (m x) + C sin h (m x)
1 2
θ =C
b 1
T =T at x = L θ = T −T
L L L ∞
θ ( x) = C cos h (m x) + C sin h (m x)
1 2
θ − θ cos h (m L)
C = L b
2 sin h (mL)
θ − θ cos h (m L)
θ ( x) = θ cosh (m x) + L b sin h (m x)
b sin h (mL)
[
θ cos h (m x) sin h (mL) + θ − θ cos h (m L) sin h (m x
θ ( x) = b L b
]
sin h (mL)
θ sin h m( L − x) + θ sin h (m x)
θ ( x) = b L
sin h (mL)
Heat transfer
L
Q = ∫ h ( P dx) (T ( x) − T )
∞
o
L
Q = ∫ h P θ ( x) dx
o
L θ sin h m( L − x) + θ L sin h (m x)
Q = ∫hP b dx
o
sin h ( mL )
hP − θ b cos h m( L − x) θ cosh (m x) L
Q= )+ L )
sin h (mL) m m o
Q=
hP
m sin h (mL)
[
− θ (1 − cos h mL) + θ ( cos h (m L) − 1)
b L
]
Q=
hP
[
θ (cos h mL − 1) + θ ( cos h (m L) − 1)
m sin h (mL) b L
]
Q=
hP
[
(θ + θ ) (cos h mL − 1)
m sin h (mL) b L
] θ = T −T
b b ∞
θ
L
= T −T
L ∞
(cos h mL − 1)
Q = (T − T ) + (T − T ) h PkA
b ∞ L ∞ L sin h (mL) (HMTDB Page No 50)
Fin efficiency
The fin efficiency is defined as the ratio of the energy transferred through a real fin to
that transferred through an ideal fin. An ideal fin is thought to be one made of a perfect or
infinite conductor material. A perfect conductor has an infinite thermal conductivity so that the
entire fin is at the base material temperature.
Q hPkA (T − T ) 1 hP
η= real
= b ∞ = m= (HMTDB Page No 50)
Q h P L (T − T ) mL kA
ideal b ∞
REFERENCES
1. Heat transfer-A basic approach, Ozisik, Tata McGraw Hill, 2002
2. Heat transfer , J P Holman, Tata McGraw Hill, 2002, 9th edition
3. Principles of heat transfer, Kreith Thomas Learning, 2001
4. Heat and Mass Transfer Data Book, C.P Kothandarman , S Subramanyan, new age
international publishers ,2010, 7th edition
5. Fundamental of Heat and Mass transfer, M Thirumaleshwar,Pearson,2013
6. Pradeep Dutta, “HEAT AND MASS TRANSFER”, Web based course material under the
NPTEL, Phase 1, 2006.